Será o príncipe pequeno? - Priscila Keila de Mendonca (2022)
With the objective of problematizing the production of meanings and subjectivation (Orlandi) in the process of translating the book The Little Prince, from Portuguese into the Brazilian Sign Language – Libras, this research seeks a theoretical contribution in Discourse Analysis (Pêcheaux), an area of transdisciplinary work that will seek in the Theory of Adaptation (Hutcheon) and Translation (Barbosa (2020), Batalha and Pontes (2008), Derrida (2001/02), specifically in Intersemiotic Translation (Jakobson), basic notions for the discussion of the process and make the final product. Thus, in addition to the specific aspects of the theories mentioned, in a qualitative analysis, Foucault's archeogenealogy (2015) will be activated so that it can be decomposed media productions and excavate the possible meanings marked by the subjectivity of the translator/listening actor in parallel with the meanings and subjectivities of the deaf translator/actor. The book “The Little Prince” by Antoine Saint-Exupéry, was published in English and French in the year 1943 by Reynal & Hitchcock, while its author was in exile in North America, was first translated into Portuguese by Dom Marcos Barbosa, in 1952 by publishing house Agir. For the composition of this work the following versions were used: - Book printed in Portuguese: 49th edition. Nova Fronteira Publisher: Rio de Janeiro, 2015; - Youtube video with translation/adaptation in Libras: Accessibility Project in Public Libraries: São Paulo, 2016; and - Video-book with translation/interpretation in Libras: Editora Arara Azul: São Paulo, 2013. Our main aim is to understand how constitutive and identity differences go beyond Intersemiotic Translation.